2015
DOI: 10.1111/pere.12071
|View full text |Cite
|
Sign up to set email alerts
|

“I know you're kidding”: Relationship closeness enhances positive perceptions of teasing

Abstract: Feeling close in a relationship may enhance perceptions of teasing within that relationship. In Study 1, participants recalled instances of teasing-as both teaser and target-in close and nonclose relationships. Participants perceived teases in close relationships more positively and better intentioned than those in nonclose relationships, as both teaser and target. The discrepancy between teasers and targets in perceptions of intent was also reduced by felt closeness. In Study 2, interaction partner closeness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…The results of the present study demonstrated that various factors play a role in creating marriage life satisfaction among infertile couples so that paying attention to them can play an important role in facilitating good mental well-being concerning marriage. The findings of the present study support various previous findings in the literature (Cann and Collette 2014;Ghadami and Khalatbari 2015;Gorman and Jordan 2015;Homaei et al 2016). The results indicated the importance of attention to the psychological health of infertile couples.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the present study demonstrated that various factors play a role in creating marriage life satisfaction among infertile couples so that paying attention to them can play an important role in facilitating good mental well-being concerning marriage. The findings of the present study support various previous findings in the literature (Cann and Collette 2014;Ghadami and Khalatbari 2015;Gorman and Jordan 2015;Homaei et al 2016). The results indicated the importance of attention to the psychological health of infertile couples.…”
Section: Discussionsupporting
confidence: 92%
“…According to the WHO (2009), it is time to go beyond diagnosis and clinical interventions related to infertile couples and to focus on the psychological factors associated with fertility problems and improving the quality of life for infertile individuals. A careful perusal of literature shows that optimism and humor play a key role in infertile couples' marital life and their positive and negative emotions and feelings (Ghadami and Khalatbari 2015;Gorman and Jordan 2015;Hills and Argyle 2001;Safari 2016;Saroglou et al 2010).…”
mentioning
confidence: 99%
“…Nevertheless, due to its playful/aggressive nature, even well-intentioned prosocial teasing may sometimes be interpreted as hostile behaviour. This might explain why teasing occurs predominantly among friends (Carlson-Jones and Burrus -Newman 2005;Gorman and Jordan 2015;Van Vleet and Feeney 2015), as there is a lower probability of negative effects among people who know and like each other (Keltner et al 1998(Keltner et al , 2001. Consequently, the perception of prosocial intent is felt to be greater where friendship exists (Carlson-Jones and Burrus -Newman 2005).…”
Section: Teasingmentioning
confidence: 99%
“…Play, as a core process of organizing, is getting increasing attention among organization scholars and practitioners lately, as it is studied as an alternative form of knowledge production, knowledge-sharing, and learning. In the workplace context, scholars have already revealed how play enhances creativity (Mainemelis & Ronson, 2006), makes decision-making more flexible and helps relating to unknown future (Andersen & Pors, 2014, 2015, develops norms and ethical orientation (Statler et al, 2009) and supports the well-being of the employees (Costea et al, 2005). Still, workplace play is blurred with gamification efforts, playful design or top-down management practices neglecting the fact that what is said to be a game or a play activity is not always the same as what is perceived as play for real from the participants' perspectives.…”
Section: Introductionmentioning
confidence: 99%